(untitled) (Argos, 2023)
Aristarchus of Samothrace, now considered the founder of modern philology, questioned the authenticity of the dialogue between Helen and Aphrodite in the third book of the Iliad. The grammarian athetized lines 396-418 on four grounds. Our main hypothesis is that his arguments, which we intend to carefully analyze here, are headed in the right direction, as they focus on elements that have neither precedent nor equal within the Homeric world. Although Aristarchus could not express it in these terms, the passage is indeed peculiar because it deviates from the expectations of the archaic Greek cultural code.